Learning from positive deviance: a qualitative multisite study of simulation practice in paediatric departments - Anders Lund Schram; Rune Dall Jensen; Maria Louise Gamborg; Eve Purdy; Morten Lindhard; Victoria Brazil (Journal of Healthcare Simulation, 2026)
Introduction Simulation-based team training (SBTT) is widely used to strengthen collaborative clinical work, yet departments vary in the extent to which SBTT becomes part of everyday practice. Existing studies describe enabling organisational conditions, but there is less insight into how simulation is handled in daily work. This study examined departments where SBTT appeared to gain a stronger foothold during a region-wide initiative. We aimed to understand the local work through which simulation became part of departmental practice in these departments. Methods An interview study was conducted in four paediatric departments in Denmark during a region-wide, one-year SBTT initiative. Relative to the wider project data, two departments were characterised by a marked increase in registered simulation activity, while two showed larger improvements in selected dimensions of patient safety culture. These patterns were used as distinct positive deviance entry points for qualitative inquiry rather than as evidence of success in themselves. Eighteen staff were interviewed, including clinicians participating in sessions, local facilitators, managers and simulation programme leads. Data were analysed thematically using Braun and Clarke’s reflexive approach. Results Analysis showed how SBTT became workable through ongoing organisational adjustment. Simulation activity stabilised when responsibility for coordination was explicit and when small openings in daily schedules were created for preparation and delivery. Regular participation also gave staff opportunities to speak with one another in ways that differed from everyday clinical interaction. Participants described how these encounters influenced communication and reflection in routine work. Staff also linked SBTT to greater continuity in how demanding situations were approached, particularly when events were high-stakes or disrupted routine work. Discussion SBTT appeared to gain a stable place when staff and managers repeatedly adjusted simulation to local clinical pressures. Continued engagement was supported by practical organisational work and by staff recognising simulation as relevant to the situations they encountered in practice. Rather than pointing to a fixed model for implementation, the findings suggest that SBTT may acquire significance beyond the scenario room when departments keep making simulation workable. These insights may help departments examine the local conditions that allow SBTT to become part of routine practice.